Software Requirement Prioritization: A Critical Study on Its Techniques - Sandanasamy, A; Selvi, R. Thamarai (International Journal of Computer Sciences and Engineering, 2025)
Software has become an indispensible element of day-to-day life. As users of the software are increasing, the need of the software is also getting increased. Developing software that meets the needs of the users is an cumbersome task for a software developer. Since the complexity of the software has increased, the intricacy of the requirement also has increased. As the market needs meet changes, software development team has to meet the changes in the requirements. Hence the developing team faces the challenge to prioritize the requirements in order to produce a risk-free software. This study describes the techniques and methods used in prioritizing the requirements